Analysis of the Epidemiology of Brucellosis in Uzbekistan and Development of Preventive Measures - Azimovna, Berdiyeva Dilrabo; Lazizovna, Rashidova Mehrangiz (American Journal of Biomedicine and Pharmacy, 2025)
This research is dedicated to analyzing the epidemiology of brucellosis in Bukhara region during 2015–2025 and developing preventive measures. Epidemiological, serological, and laboratory data were analyzed. The results show that in recent years the incidence of brucellosis has significantly decreased. This is associated with preventive measures, vaccination of animals, and raising awareness about sanitation and hygiene. The findings can be used to reduce the spread of brucellosis and improve infection control strategies.